Urgensi Adaptabilitas dan Resiliensi Karier pada Masa Pandemi - Rina Nurhudi Ramdhani; Andi Kiswanto (Indonesian Journal of Educational Counseling, 2020)
THE IMPORTANCE OF ADAPTABILITY AND CAREER RESILIENCE DURING THE PANDEMIC. The main focus of this article is to explore the importance of career adaptability and resilience in dealing with a pandemic. Through various sources of literature it was found that career adaptability and resilience not only as a goal but also as a process. The development of career adaptability and resilience requires professional intervention through career guidance and counseling.